Analysis of the Space Frame Structure of the Cileungsi Fly Over Tower Bogor Regency - Budiono Budiono; Singgih Irianto; Budi Arief; Lirawati Lirawati (Green Publisher Indonesia, 2024)
This research is part of the plan of the Bogor Regency government, especially Cileungsi District, in arranging the Cileungsi flyover which is currently filled with garbage and used as a shadow terminal, making the area look slum. The arrangement effort is made to create a comfortable, neat flyover that can become an icon of Bogor Regency. The research aims to produce a portal tower flyover design that is aesthetic, unique, sturdy, and meets the strength and stability standards of the structure according to local conditions. The analysis was carried out using SAP2000 software to model the three-dimensional space structure and identify the strength, stability, and deflection of the structure. The LRFD (Load Resistance Factor Design) method is used in calculating the bearing capacity of the structure. The results of the analysis show that the space frame structure made of steel pipes has stable and rigid behavior, meeting all work loads, including dead loads, live loads, wind, and earthquakes. The design of the 13-meter deep pile foundation has also been proven to be able to withstand loads safely. The design of the space frame structure made of steel pipes for the Cileungsi flyover portal tower is declared strong, stable, and safe to implement. This structure can be used as a new icon for Bogor Regency, especially Cileungsi District. The implementation of this design requires detailed depiction as a construction guideline in the field.